Association Between Stress Level, Sleep Quality, Physical Activity With Cardiorespiratory Fitness In Medical Students: A Cross Sectional Study - Ermin Rachmawati; Alvi Milliana; Sefira Maulida Filzah; Adhitya Wishnu Kresnanda (Journal of Islamic Medicine, 2023)
Introduction Modern life style and high burden of academic tasks contribute to the upsurge of stress, poor sleep quality, lack of sufficient physical activity in medical student society nowadays. The unhealthy life style act as one cardiovascular risk factor which can be predicted using Cardiorespiratory Fitness (CRF) examination. Objectives to identify the association between stress, sleep quality, physical activity with CRF level among medical students. Design The cross-sectional data was collected between September until November 2021. A total of 38 male and 73 female students of Faculty of Medicine and Health Sciences UIN Maulana Malik Ibrahim Malang were participated in this study. Stress level was assessed with DASS-21, sleep quality with PSQI, physical activity with GPAQ questionnaire.  The level of CRF was measured using the Harvard Step Test. Statistical analysis for bivariate correlation ordinal scale was tested using Spearman Rank. Results 83 participants (74,8%) had low CRF. Meanwhile, 76 participants (68,5%) experienced no stress. In addition, 75 participants (67,6%) had poor sleep quality. A total number of 79 participants (71%) had low physical activity. There was no significant correlation between stress level, sleep quality, physical activity with CRF ( p=0,962; 0,772; 0,114, respectively). The participants who had low physical activity and low CRF was found in 56 participants (50,45%). Conclusions There was no association between stress level, sleep quality, physical activity with CRF among medical students. Keywords: Cardiorespiratory fitness; Stress; Sleep quality; Physical activity.